Hubungan Penggunaan Alat Pelindung Wajah (Face Shield) dengan Terjadinya Keluhan Penglihatan pada Pekerja Bengkel Las di Kecamatan Maulafa - Julion Meliatri Baba; Johny A. R. Salmun; Yendris K. Syamruth (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Welding workers are jobs that have a very high level of risk with the occurrence of vision complaints. This research is an analytic survey study using the cross-sectional method with the aim of analyzing the relationship between the use of face shields and the occurrence of vision complaints in welding workshop workers in Maulafa District. In this study, the total population was 115 welding workshop workers in Maulafa District. The sampling technique uses the Lemeshow formula so that the sample in this study is 89 respondents. The results of the chi-square test show that of the six research variables studied. four variables have a relationship with vision complaints. where is the p value of the variable length of service (p=0.019), length of exposure (p=0.000), use of welding goggles (p=0.048) use of face shields (p=0.000) with the occurrence of vision complaints and two variables had no relationship, namely age (p=0.157) and level of education (0.754). It is hoped that the relevant agencies can provide education related to occupational health and safety and the importance of using PPE when carrying out work to prevent vision complaints due to the welding process and also for welding workshop business owners to provide eye protection and face shield masks in accordance with the number of workers.